Chemical Pulps for Writing and Printing Papers from a Mixture of Broad-leaved Woods - Guha, S. R. D.; Singh, Man Mohan; Saxena, V. B. (Indian Forester, 1961)
Laboratory experiments on the pulping of mixture of broad-leaved woods from Madhya Pradesh for the manufacture of writing and printing papers by the sulphate process followed by multistage bleaching are described.